Предмет: Алгебра,
автор: blict
Упрости выражение (5a3−3b)⋅2b−3b⋅(13a3−4b).
Ответы
Автор ответа:
2
(5a3-3b)•2b-3b•(13a3-4b)=
2b•(5a•3-3b)-3b•(39a-4b)=
2b•(15a-3b)-3b•(39a-4b)=
b•(2(15a-3b)-3(39a-4b))=
b•(30a-6b-117a+12b)=
b•(-87a+6b)=
b•(-3(29a-2b))=
-3b•(29a-2b)
2b•(5a•3-3b)-3b•(39a-4b)=
2b•(15a-3b)-3b•(39a-4b)=
b•(2(15a-3b)-3(39a-4b))=
b•(30a-6b-117a+12b)=
b•(-87a+6b)=
b•(-3(29a-2b))=
-3b•(29a-2b)
Похожие вопросы
Предмет: Алгебра,
автор: CLEO99
Предмет: Математика,
автор: zagitovaelvina0
Предмет: Математика,
автор: valeria07062001
Предмет: Английский язык,
автор: Аноним
Предмет: Химия,
автор: аофедшй